Do Children with Better Inhibitory Control Donate More? Differentiating between Early and Middle Childhood and Cool and Hot Inhibitory Control - Hao, Jian (Frontiers in Psychology, 2017)
Inhibitory control may play an important part in prosocial behavior, such as donating behavior. However, it is not clear at what developmental stage inhibitory control becomes associated with donating behavior and which aspects of inhibitory control are related to donating behavior during development in early to middle childhood. The present study aimed to clarify these issues with two experiments. In Experiment 1, 103 3- to 5-year-old preschoolers completed cool (Stroop-like) and hot (delay of gratification) inhibitory control tasks and a donating task. The results indicated that there were no relationships between cool or hot inhibitory control and donating behavior in the whole group and each age group of the preschoolers. In Experiment 2, 140 elementary school children in Grades 2, 4 and 6 completed cool (Stroop-like) and hot (delay of gratification) inhibitory control tasks and a donating task. The results showed that inhibitory control was positively associated with donating behavior in the whole group. Cool and hot inhibitory control respectively predicted donating behavior in the second and sixth graders. Therefore, the present study reveals that donating behavior increasingly relies on specific inhibitory control, i.e. hot inhibitory control as children grow in middle childhood.